UJI PUPUK N DAN MACAM BENTUK PUPUK KOTORAN KAMBING TERHADAP PERTUMBUHAN DAN HASIL KANGKUNG - ENDANG SUPRAPTI; TYAS SUMARAH KD (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2018)
Goat manure is a fertilizer that works to improve the yield of plants, and can replace the use of inorganic fertilizers. This study aims to determine the effect of giving various forms of goat manure to the growth and yield of Convolvulus. The research was conducted in Kliteh Village, Sragen, with a height of 109 m above sea level with soil type vertisol. The study used Completely Randomized Design with single factor and repeated 3 times. The treatments were Fertilizer N (N1), Whole Nursery Cow Fertilizer (N2), Giving Fertilized Goat Pupuk (N3), Water Supply of Goat Goat (N4) and Water Supply + Goat Dung (N5). The results showed that Fertilizer N gave the best result compared to the treatment of various types of goat manure on the crop yields, the number of leaves, the weight of fresh stover and the weight of the dried straw, while the shape of the whole goat manure gave the best yield on the crop yield convolvulus than other forms of manure goat.